Therapeutic Potential of Bovine Amniotic Membrane in Wound Healing: Insights from a Mouse Model - Dongwoo Yu; Ye Jin Kwon; Chi Heon Kim; Inbo Han; Jong-Moon Hwang; Kyoung-Tae Kim (Cells)
Wound healing involves complex interplay between cellular and molecular events. In this study, we investigated the therapeutic potential of the bovine amniotic membrane (BAM) in wound healing using a mouse model. Twelve male C57BL/6 mice were divided into four groups: negative control (Vehicle), positive control (DuoDERM Extra Thin®), amniotic membrane attachment (Amniotic Membrane), and compressed amniotic membrane attachment (Amniotic Membrane with Compression). The dorsal skin of each mouse was excised and wound-healing parameters were assessed over a two-week period. Our results revealed that the Amniotic Membrane and Amniotic Membrane with Compression groups demonstrated significant sustained reductions in the wound area compared to the Vehicle group. These reductions were more pronounced than those observed in the DuoDERM group. Histopathological analysis revealed advanced wound healing characteristics in the BAM-treated groups. Immunohistochemical analysis demonstrated elevated expression levels of wound healing markers (including α-smooth muscle actin, collagen type III, SMAD 1/5/8, and SMAD 2/3) in the BAM-treated groups compared to the control and DuoDERM groups. Conversely, cluster of differentiation 4 levels were significantly lower in BAM-treated groups. Overall, our findings highlight the therapeutic efficacy of BAM and compression in promoting wound healing. Thus, BAM offers a promising therapeutic approach for enhancing wound healing outcomes in clinical settings, potentially by modulating key wound healing pathways and processes.